2023
DOI: 10.3390/su151511581
|View full text |Cite
|
Sign up to set email alerts
|

Precursor Signal Identification and Acoustic Emission Characteristics of Coal Fracture Process Subjected to Uniaxial Loading

Abstract: In deep underground mine engineering, the critical warning signals before the sudden failure of coal are crucial to predict coal or rock dynamic catastrophes and to help the coal industry grow sustainably. Therefore, with the objective of accurately identifying the precursor signals of coal fracture, a uniaxial compression test was adopted. Tests were performed on multiple sets of raw coal samples, and acoustic emission (AE) technology was used to capture the deformation and destruction courses of the coal sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…But the problem is the complexity of implementation of such systems. These systems have a high cost [94][95][96][97][98][99][100][101]. The use of monitoring systems implies changes in every step of the production process.…”
Section: Delay (2000); }mentioning
confidence: 99%
“…But the problem is the complexity of implementation of such systems. These systems have a high cost [94][95][96][97][98][99][100][101]. The use of monitoring systems implies changes in every step of the production process.…”
Section: Delay (2000); }mentioning
confidence: 99%
“…Numerical simulations by Tang et al through a coupled thermal-water-mechanical damage model and its application to rock column stability analysis 21 , showed test behavior similar to that observed in the laboratory; Liang et al 22 found that the percentage of shear-type cracks gradually increased with the increase of the stress difference of the initial stress state through the particle flow analysis of the thermal rupture characteristics of granite with different stress states under the action of thermal coupling. Some scholars have used technology to measure more detailed data, and used acoustic emission technology to capture the deformation and failure process of coal samples 23 . CT scan is used to scan the internal structure of the specimen to study the influence of uniaxial stress on the structure of coal pore fracture system 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the fractal dimension gradually decreased after the initial fluctuations in the loading stage, reaching its minimum when damage occurred [17]. Applying the critical slowing-down theory, Kong et al [18] found that it is easier to identify the variance mutation point in the AE signal prior to coal sample failure compared to the autocorrelation coefficient. In their research, Zhou et al [19] explored the correlation between AE parameters of coal samples and disturbance amplitude.…”
Section: Introductionmentioning
confidence: 99%